Functional Magnetic Resonance Imaging Adaptation Reveals the Cortical Networks for Processing Grasp-Relevant Object Properties. (29th January 2013) - Monaco, Simona; Chen, Ying; Medendorp, W.P.; Crawford, J.D.; Fiehler, Katja; Henriques, Denise Y.P.
Abstract : Grasping behaviors require the selection of grasp-relevant object dimensions, independent of overall object size. Previous neuroimaging studies found that the intraparietal cortex processes object size, but it is unknown whether the graspable dimension (i.e., grasp axis between selected points on the object) or the overall size of objects triggers activation in that region. We used functional magnetic resonance imaging adaptation to investigate human brain areas involved in processing the grasp-relevant dimension of real 3-dimensional objects in grasping and viewing tasks. Trials consisted of 2 sequential stimuli in which the object's grasp-relevant dimension, its global size, or both were novel or repeated. We found that calcarine and extrastriate visual areas adapted to object size regardless of the grasp-relevant dimension during viewing tasks. In contrast, the superior parietal occipital cortex (SPOC) and lateral occipital complex of the left hemisphere adapted to the grasp-relevant dimension regardless of object size and task. Finally, the dorsal premotor cortex adapted to the grasp-relevant dimension in grasping, but not in viewing, tasks, suggesting that motor processing was complete at this stage. Taken together, our results provide a complete cortical circuit for progressive transformation of general object properties into grasp-related responses.